إشكالية الشورى والديمقراطية عند السلفية - الحباس, سليمان أبوبكر صالح محمد (Tobruk University Journal of Social and Human Sciences, 2021)
The problem of shura and democracy is limited to two currents: the first is a current that considers that the shura differs from democracy in many respects, including concept and method of application, and the second movement considers that shura and democracy never meet either form or content.     Each current believes that it is right, and works hard to exclude the other current, Salafism adheres to the islamic evidence from the Qur'an and the Prophet's Sunnah, while the other current sees that laws and religions are positive that support democracy without shura, but there are those who integrate them with each other in order to solve this problem.    Therefore, this research is an attempt at the divergent Salafist views, and each current has its own approach, including those who adhere to the concept of shura and democracy from a legitimate point of view, some of whom adhere to the traditional concept of Shura, and another current that uses the critical approach through the methodology of rereading the text and this is the rational current.